2017
DOI: 10.1021/acs.energyfuels.6b03137
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on Coal Char Combustion in a Microfluidized Bed

Abstract: The intrinsic kinetics of char combustion were commonly investigated using thermogravimetric analysis (TGA) in previous works at low temperatures to prevent oxygen limitations and temperature deviation. However, the low temperatures caused excess test time because the reaction rate was too slow. In this study, the microfluidized bed (MFB), which has effective heat and mass transfer, was used to investigate the intrinsic kinetics of char combustion at a higher temperature within less time. TGA was used to check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Raw coal was ground and sieved to a diameter of 75–100 μm. We have investigated the effect of char diameter on char conversion in such MFBs in our previous study 24 and found that the carbon conversion rate did not increase with decreasing the particle size below 100 μm, indicating that the internal diffusion limitation could be disregarded when the particle size was less than 100 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Raw coal was ground and sieved to a diameter of 75–100 μm. We have investigated the effect of char diameter on char conversion in such MFBs in our previous study 24 and found that the carbon conversion rate did not increase with decreasing the particle size below 100 μm, indicating that the internal diffusion limitation could be disregarded when the particle size was less than 100 μm.…”
Section: Methodsmentioning
confidence: 99%
“…where X is the conversion in time t. In this work, a similar analysis to Fang et al [27] is used, where the conversion is determined from the measured output gas composition instead of sample mass, as the gas composition is measured online unlike of the sample mass. All the carbon containing species n are added together for each time step i and compared to the total released carbon, presented in Equation 4.…”
Section: Reactivity Analysismentioning
confidence: 99%
“…Kijo-Kleczkowska et al [26] studied reactivity of pelletized samples suspended in an updraft reactor. Fang et al [27] utilized a small fluidized bed to study reactivity of coal char. Adamczyk et al [28] presented a method where the fuel particles are dropped into a horizontal "windtunnel" and changes in particle trajectories are analyzed to determine the reaction rate of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to TGA, the MFBRA features: (1) high rates of heat and mass transfer, (2) capability of online instantaneously pulse feeding and super‐fast heating of powder reactant to bed temperature, (3) negligible external diffusion inhibition, and (4) fast on‐line measurement 19,20 . Until now, it has been successfully applied to study the mechanisms and kinetics of a variety of gas–solid reactions, including pyrolysis, 22–24 gasification, 14,25,26 combustion 27,28 of coal, biomass, oil shale and chars, calcination, 11,20 and reduction 29–32 of various materials as well as catalytic gas–solid reactions, 33,34 etc. These applications have demonstrated that MFBRA is effective, reliable, and adaptable to various gas–solids reactions.…”
Section: Introductionmentioning
confidence: 99%